PENGARUH MOTIVASI TERHADAP PRESTASI BELAJAR MAHASISWA POLITEKNIK ANIKA PALEMBANG - Imelda, Imelda; Cahyani, Eni (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study aims to determine the effect of motivation on student achievement, it is expected that the results can provide information for Higher Education to see factors of student learning motivation that can improve student achievement and contribute to further research. The population of this research is Anika Polytechnic students, data collection using methods and techniques by distributing questionnaires to students of the Informatics Management study program 2014/2015 academic year. Other data used is a recap of the CPI and absenteeism. Quantitative analysis methods using multiple linear regression. The results of the analysis show that motivation from both internal and external factors has a significant and positive effect on student achievement